Effect of Celebrity Endorsements on Consumers Purchase Decision in Nigeria - Ifeanyichukwu, Chioma Dili (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
The use of celebrities is one of the very many marketing strategies employed by marketers in todayâs business environment. The Nigerian economy has witnessed increased launching of consumer products. No doubt, intense competition in the business environment among various products and services has led to organizations endorsing deals/ambassadors. Nowadays, we hear the term âbrand ambassadorsâ more often than usual. Celebrity endorsement is one of the very many features of modern marketing. This study attempts to determine the effect of celebrity endorsement on consumer purchase of a product. 200 young adults were conveniently selected as respondents for the study. Regression was used to test for the significance of the hypotheses generated.